Nematic Mesogen with 1,3,4-Oxadiazole Unit as Stationary Phase in Gas-Liquid Chromatography - Jasim, Zainab; R. Jber, Nasreen (Al-Nahrain Journal of Science, 2021)
This paper is the first that deals with the new synthesis of nematic liquid crystal titled bis-[5-yl-phenylbenzidine-4`-butyloxyphenly-2-yl-1,3,4-oxadiazole] and secondly discusses research on materials that can be used in stationary phase by using (GLC) as a type of chromatography. The usage of bis-[5-yl-phenylbenzidine-4`-butyloxyphenly-2-yl-1,3,4-oxadiazole] nematic phase has resulted in a lot of superb separations of a lot of poly aromatic hydrocarbons. The retention time change in an unusual way with temperature, appearance a significant increase at the normal liquid transmission point; as expected, that impact is reduced with further planar compounds. FT-IR and 1HNMR were used to characterize the synthesized chemical structure, and POM and DSC were used to investigate the liquid crystalline characteristics.